Reducing solid waste through waste banks: an empirical study in Kepulauan Riau, Indonesia. Issue 1 (April 2021) - Yudiatmaja, W E; Edison; Samnuzulsari, T; Yudithia; Rezeki, S R I; Suyito; Akbar, D; Alfiandri, A
Abstract: To overcome the solid waste problem, many city governments initiate and facilitate waste banks. Various studies have sought citizen participation in waste banks, but there is little attention to understanding how the coexistence of social capital can encourage waste banks' practice. This study, therefore, aims at examining the social capital of the urban communities in the business process of waste banks. We looked in-depth at the practice of six waste banks in Tanjungpinang City, Kepulauan Riau, Indonesia. A series of interviews were carried out on the stakeholders of waste banks, such as management, customers, citizens, and households. We suggest that a number of social capitals shape the business process of waste banks, including trust, norms, social networks, and gotong royong. This research has a novel for the study of community-based waste management by considering the urban community's social capital. Our study also has a worthy recommendation to the local government in managing waste management by corroborating social capital.